2007
DOI: 10.1002/pc.20331
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic response of nanocomposite poly(vinyl acetate)‐hydroxyapatite with varying particle shape—Dynamic strain softening and modulus recovery

Abstract: Dynamic-strain softening known as the Payne effect was investigated in the case of poly(vinyl acetate)-hydroxyapatite (PVAc-HA) model nanocomposites in which the nanoparticles served as reversible physical crosslinks. HA nanofillers with different particle shape and with size ranging from 5 to 60 nm were used. Filler concentration in PVAc nanocomposites was limited to maximum of 5 vol%. Dynamic-mechanical spectra were recorded as a function of structural variables, strain amplitude, and test temperature using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 15 publications
5
27
0
Order By: Relevance
“…This can be attributed to the chain immobilization in the vicinity of filler surfaces, which is consistent with results published in literature [11,[13][14][15]. It was also demonstrated that the particle size affects thermal stability of the Mg(OH) 2 filled EVA significantly.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This can be attributed to the chain immobilization in the vicinity of filler surfaces, which is consistent with results published in literature [11,[13][14][15]. It was also demonstrated that the particle size affects thermal stability of the Mg(OH) 2 filled EVA significantly.…”
Section: Discussionsupporting
confidence: 91%
“…Dolan [12] demonstrated that inorganic powder can suppress the methane burning with the magnitude of the effect proportional to the particle specific surface area. As it has already been shown by Kalfus and Jancar [13][14][15], filler nanoparticles may cause considerable immobilization effects in the polymer matrix even in the case of weak filler-particle interaction. As a consequence, one can observe sharp enhancement of composite elastic modulus.…”
Section: Introductionmentioning
confidence: 87%
“…There is a large literature showing a strong softening of NP-filled networks where the effect is temperature dependent and where the effect is observed following a small extent of deformation. The Payne effect is often attributed to the breakdown of particle-polymer associations within the network,68 as in our model, or the irreversible breakup of NP clusters within the network. The breakup of the physical associations should be reversible while this is not the case for the breakup of the NP clusters.…”
Section: Resultsmentioning
confidence: 82%
“…So far, serious attempts to investigate the reinforcing mechanism in polymer nanocomposites have been predominantly restricted to systems with amorphous matrices [1][2][3][4][5][6][7][8][9][10][11][12][13][14]. In these matrices above their T g , the chains can undergo segmental immobilization induced even by weak interactions on the large filler-matrix internal interface.…”
Section: Introductionmentioning
confidence: 99%